Germination stimulation of striga gesnerioides seeds by hosts and nonhosts - Berner, D.K.; Williams, O.A. (Scientific Societies, 1998)
Cowpea (Vigna unguiculata) is an important source of protein in Africa, but production is hindered by the parasitic plant Striga gesnerioides. Crop rotation with non-host cultivars, selected to stimulate parasite seed germination, is being used successfully to control other Striga spp. and may have potential to control S. gesnerioides. Little information has been available on nonhosts of S. gesnerioides that are capable of stimulating germination of parasite seeds. A laboratory procedure was used to evaluate species and cultivars for their ability to stimulate S. gesnerioides seed germination. Genotypes of all Vigna spp. tested stimulated parasite seed germination. Some genotypes of the non-host species Cajanus cajan, Lablab purpureus, Sphenostylis stenocarpa, and Sorghum bicolor also stimulated parasite seed germination. One cultivar of Sorghum bicolor stimulated significantly more germination than any other cultivar or species. Control of S. gesnerioides through rotation with selected non-host cultivars has potential if selection is done with the parasite isolate(s) from the locality of intended use. When seeds of single-plant isolates of S. gesnerioides were tested against roots of seedlings from Sorghum bicolor landraces and from a susceptible cowpea cultivar, only specific isolate and plant combinations resulted in parasite seed germination. These specific interactions have broader implications for parasite survival.